CYP2D6 allele frequencies, copy number variants, and tandems in the population of Hong Kong. Issue 1 (1st August 2018) - Chan, Wing; Li, Man S.; Sundaram, Senthil K.; Tomlinson, Brian; Cheung, Pik Y.; Tzang, Chi H.
Abstract : Background: CYP2D6 plays a crucial role in drug metabolism of several drugs. It is known to be highly polymorphic with enzymatic activity ranging from poor to ultrarapid metabolic rates. While the frequencies of CYP2D6 alleles are generally known in different Asian populations, data on frequencies of the copy number variations (CNV) and tandems in CYP2D6 in which they occur are less well studied in these populations. Methods: A cohort of 800 consecutive, unrelated individuals were referred to Prenetics Limited (Prenetics) iGenes test by physicians in Hong Kong as part of their care with informed consent. These clinical samples were deidentified prior to further analysis. Genotyping and copy number determination of CYP2D6 were performed using target specific TaqMan ® SNP genotyping and copy number assays. The phenotypes of CYP2D6 were predicted based on its genotypes and is dependent on the biallelic expression of alleles. Results: Among the Asian group (n = 735, 92%), the observed frequency of CYP2D6*36‐*10 tandems was 34.1%. We also identified duplication of CYP2D6 alleles in 86 (11.7%) individuals of the study cohort. The frequency of all CYP2D6 duplicated alleles was 154 (10.5%) while only 28 (1.9%) of the duplications were of functional alleles (ie CYP2D6*1 and CYP2D6*2 ). Conclusion: The present study provides a comprehensive analysis on the occurrences of CNV and tandems of the CYP2D6 gene in the Hong Kong population. The results contribute to the overall knowledge of pharmacogenomics and may accelerate the implementation of precision medicine in Asia.